Representing the good German in literature and culture after 1945 : altruism and moral ambiguity - Ó Dochartaigh, Pól; Schönfeld, Christiane (Studies in German literature, linguistics, and culture., 2013)
In the aftermath of the Second World War, both the allied occupying powers and the nascent German authorities sought Germans whose record during the war and the Nazi period could serve as a counterpoint to the notion of Germans as evil. That search has never really stopped. In the past few years, we have witnessed a burgeoning of cultural representations of this "other" kind of Third Reich citizen - the "good German" - as opposed to the committed Nazi or genocidal maniac. Such representations have highlighted individuals' choices in favor of dissenting behavior, moral truth, or at the very least civil disobedience. The "good German's" counterhegemonic practice cannot negate or contradict the barbaric reality of Hitler's Germany, but reflects a value system based on humanity and an "other" ideal community. This volume of new essays explores postwar and recent representations of "good Germans" during the Third Reich, analyzing the logic of moral behavior, cultural and moral relativism, and social conformity found in them. It thus draws together discussions of the function and reception of "Good Germans" in Germany and abroad. Contributors: Eoin Bourke, Manuel Bragança, Maeve Cooke, Kevin De Ornellas, Sabine Egger, Joachim Fischer, Coman Hamilton, Jon Hughes, Karina von Lindeiner-Strásky, Alexandra Ludewig, Pól O Dochartaigh, Christiane Schönfeld, Matthias Uecker. Pól O Dochartaigh is Professor of German and Dean of the Faculty of Arts at the University of Ulster, Northern Ireland. Christiane Schönfeld is Senior Lecturer in German and Head of the Department of German Studies at Mary Immaculate College, University of Limerick.